2010
DOI: 10.1016/j.neuron.2010.10.013
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Alzheimer Disease: Back to the Future

Abstract: Three decades of genetic research in Alzheimer disease (AD) have substantially broadened our understanding of the pathogenetic mechanisms leading to neurodegeneration and dementia. Positional cloning led to the identification of rare, disease-causing mutations in APP, PSEN1, and PSEN2 causing early-onset familial AD, followed by the discovery of APOE as the single most important risk factor for late-onset AD. Recent genome-wide association approaches have delivered several additional AD susceptibility loci tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
518
0
16

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 738 publications
(545 citation statements)
references
References 118 publications
11
518
0
16
Order By: Relevance
“…TGF-b1 contributes to Ab precursor expression and Ab deposition (van der Wal et al 1993;Wyss-Coray et al 1997;Burton et al 2002); however, TGF-b1 attenuates microglia clustering to Ab aggregates, and TGF-b1 expression in astrocytes causes a reduction in overall plaque burden (Wyss-Coray et al 2001;Huang et al 2010). Interestingly, TGF-b1 is enriched in plasma lipoprotein samples of apoliprotein E3 (apoE3), but occurs at a lower concentration in lipoproteins containing apoE4, a genetic risk factor for late-onset Alzheimer's disease (Tesseur et al 2009;Bertram et al 2010). Impairment in TGF-b/Smad signaling and decreased neuronal expression of TbRII are both characteristics of disease pathology, providing further evidence for a role for TGF-b in Alzheimer's disease (Tesseur et al 2006;Ueberham et al 2006;Wang et al 2010).…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…TGF-b1 contributes to Ab precursor expression and Ab deposition (van der Wal et al 1993;Wyss-Coray et al 1997;Burton et al 2002); however, TGF-b1 attenuates microglia clustering to Ab aggregates, and TGF-b1 expression in astrocytes causes a reduction in overall plaque burden (Wyss-Coray et al 2001;Huang et al 2010). Interestingly, TGF-b1 is enriched in plasma lipoprotein samples of apoliprotein E3 (apoE3), but occurs at a lower concentration in lipoproteins containing apoE4, a genetic risk factor for late-onset Alzheimer's disease (Tesseur et al 2009;Bertram et al 2010). Impairment in TGF-b/Smad signaling and decreased neuronal expression of TbRII are both characteristics of disease pathology, providing further evidence for a role for TGF-b in Alzheimer's disease (Tesseur et al 2006;Ueberham et al 2006;Wang et al 2010).…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…Further analyses of SNPs and copy number variations (CNVs) have revealed the existence of more than 200 distinct disease-causing mutations. 19,20 More recently, GWAS have revealed the association of many common polymorphisms to ND sporadic cases, providing in about 3 years more reproducible and consistent findings than 2 decades of candidate-gene-driven research. 21 However, despite the step forward, the identification of potential causative loci associated to ND by GWAS explained only a little percentage of the cases, and the 'missing heritability' issue (ie, the contribution of epigenetic modifications on gene expression) 22 is still a limitation.…”
Section: Introductionmentioning
confidence: 99%
“…2 Attempts to identify additional AD genes have been largely limited to the search for simple DNA sequence variants (mutations and singlenucleotide polymorphisms) that influence AD susceptibility or time-to-onset. 3,4 Genome-wide association studies have identified several common AD-associated polymorphisms with very small effect sizes. 5 Recent studies estimate that structural variations in the genome, including copy number variations (CNVs) 6 make a significant contribution to genetic and phenotypic variation.…”
Section: Introductionmentioning
confidence: 99%